Coelioxoides piscicauda sp. nov., a new cuckoo bee from southeastern Brazil with a key to the species of Coelioxoides Cresson (Hymenoptera: Apidae) - Rocha-Filho, Léo Correia Da; Serrano, José Carlos; Garófalo, Carlos Alberto (Zootaxa, 2017)
A new species of Coelioxoides Cresson (Apidae), Coelioxoides piscicauda sp. nov. Rocha-Filho from São Paulo State, Brazil, is described. A key to the four recognized species of the genus, C. exulans (Holmberg), C. piscicauda sp. nov., C. punctipennis Cresson, and C. waltheriae Ducke, is provided. In addition, new host records of Coelioxoides are presented as well as a compilation of published data on species of Tetrapedia Klug associated with this cleptoparasitic genus.